Effects of tropospheric ozone on loblolly pine seedlings inoculated with root infecting ophiostomatoid fungi. (December 2015) - Chieppa, Jeff; Chappelka, Art; Eckhardt, Lori
Abstract: Seedlings from four loblolly pine ( Pinus taeda L.) families were exposed in open-top chambers to charcoal-filtered air (CF), non-filtered air (NF) or air amended with ozone to 2 times ambient (2×). Two of the families used were selected for their tolerance to fungi associated with Southern Pine Decline while two were selected for their susceptibility. Seedlings were treated with five inoculation treatments: no wound (NW), wound only (W), wound + media (WM), Grosmannia huntii (GH) and Leptographium terebrantis (LT). After 118 days of exposure (AOT40 = 31 ppm-hr −1 for 2× ozone) seedling volume, dry matter, chlorophyll content, water potential and lesions were measured and analyzed using ANOVA procedures. Our results indicate that seedlings selected for their susceptibility to root infecting ophiostomatoid fungi were also more sensitive to ozone. Overall lesion length was greater on seedlings exposed to elevated ozone concentrations but was not specific to either root infecting ophiostomatoid fungi. Highlights: Loblolly pine families susceptible to fungi were also more sensitive to ozone. Lesions from the inoculations were larger in seedlings exposed to ozone. Ozone concentration had no effect on midday water potential. Ozone concentration significantly affects chlorophyll content. Ozone exposure increased seedling volume growth while inoculation had no effect. Abstract : Our study provides insight into the possible link between ozone sensitivity and susceptibility to root infecting ophiostomatoid fungi in loblolly pine.